Hidden epidermal cyst on finger joint with radiating feeding capillaries – A novel sign of epidermal cyst. - Chuh, A. (European Journal of Pediatric Dermatology, 2018)
A 15-year-old boy had been enduring an ulcerating skin lesion on the dorsal aspect of the metacarpal-phalangeal joint of his right index finger for one month. Perilesional compression resulted in chalky and foul-smelling material being expressed. Dermoscopy revealed a cyst with radiating capillaries in serpentine and coiled vascular configuration at the centre region. These findings led to the diagnosis of a ruptured epidermal cyst. Dermoscope-guided excisional biopsy for histopathology confirmed the diagnosis. Healing was prompt and uncomplicated. We thus highlight the power of epiluminescence in dermoscopy to unveil a hidden epidermal cyst, and a novel dermoscopic sign of radiating capillaries in an epidermal cyst.